Electoral Participation of Non‐National EU Citizens in France: The Case of the Nord - Kelbel, Camille (2024)
Since the 1993 Maastricht Treaty, EU citizens have the right to vote in European and local elections in the member state they reside in. In France, only about a quarter do so. Our article considers what factors explain the registration and participation of non-national citizens for the French Department of the Nord where around 35,000 non-French European citizens of voting age are living. Among them, 11,638 are registered to vote in the French municipal elections. Following the 2020 municipal elections, we have consulted the electoral rolls in each of the 648 communes to know who actually cast a vote. Based on detailed census data on each EU nationality and on other information contained on the electoral lists and rolls (age, gender, place of birth, etc.) and also contextual variables, this article seeks to identify the main factors associated with registering in the first instance and turning out to vote in the second. Our results confirm wide variation in registration and voting rates according to nationality. They also show that beyond voters’ nationality and the “usual suspects” of electoral participation, contextual factors are important predictors.